2018
DOI: 10.1002/jcp.27537
|View full text |Cite
|
Sign up to set email alerts
|

Physalin D regulates macrophage M1/M2 polarization via the STAT1/6 pathway

Abstract: The in vitro and in vivo effects of physalin D on macrophage M1/M2 polarization were investigated. In silico analysis was first performed for biological function prediction of different physalins. The results suggest physalins have similar predicted biological functions due to their similarities in chemical structures. The cytotoxicity of physalins was then analyzed based on cell apoptosis rate and cell viability evaluation. Physalin D was chosen for further study due to its minimal cytotoxicity. Bone marrow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…Herbal compound Physalin D can repolarize M1 toward M2 polarization in BMDM through STAT1 suppression and STAT6 activation (29), which consist with our study.…”
Section: Genessupporting
confidence: 90%
“…Herbal compound Physalin D can repolarize M1 toward M2 polarization in BMDM through STAT1 suppression and STAT6 activation (29), which consist with our study.…”
Section: Genessupporting
confidence: 90%
“…Moreover, anti-inflammatory, antimalarial, and antinociceptive effects of physalins have been reported (10)(11)(12). We also previously reported that Physalin D can regulate macrophage polarization towards a M2 phenotype (13). However, the effects of physalin in the skeletal system have not been reported, whereas that physalin was suppressive in macrophage activation has been (7).…”
Section: Introductionmentioning
confidence: 97%
“…In human primary macrophages derived from CD14 + PBMCs, poly (ADP-ribose) polymerase family member 14 (PARP14) silencing accelerated IFNγ induced STAT1 phosphorylation and improved M1 macrophage activation [58]. Ning Ding et al indicated that STAT1 is an important transcription factor for M1 polarization, and identified that physalin D could inhibit M1 polarization by suppressing STAT1 activation [59]. However, the role of STAT1 in upregulated M1 polarization in RSA and the underlying mechanism are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%